AFM Visualization of Mobile Influenza A M2 Molecules in Planar Bilayers - Hughes, Travis (Biophysical Society, 2004)
We report the observation of influenza A M2 (M2) incorporated in a dipalmitoylphosphatidylcholine (DPPC) supported planar bilayer on mica, formed by use of a modified vesicle fusion method from proteoliposomes and visualized with contact mode atomic force microscopy. Incubation of proteoliposomes in a hyperosmotic solution and increased DPPC/M2 weight ratios improved supported planar bilayer formation by M2/DPPC proteoliposomes. M2's extra-bilayer domains were observed as particles estimated to protrude 1–1.5 nm above the bilayer surface and <4 nm in diameter. Particle density was 5–18% of the nominal tetramer density. Movement of observable M2 particles was independent of the probe tip. The mean lateral diffusion coefficient (D) of M2 was 4.4 ± 1.0 × 10(−14) cm(2)/s. Eighty-two percent of observable particles were mobile on the observable timescale (D > 6 × 10(−15) cm(2)/s). Protein-protein interactions were also observed directly.